America Septentrionalis : concinnata juxta observationes Dñn Academiae Regalis Scientiarum et nonnullorum aliorum, et juxta annotationes recentissimas. - Lotter, Tobias Conrad, 1717-1777 (Tobiam Conr. Lotter, 1758)
Map shows known extent of North America from Greenland and Baffin Bay to New Spain and Panama; northern coast of South America, the West indies, California, and the Sargasso Sea; explorers' routes along the Pacific coast of California and New Spain, and areas of Native American habitation. Relief shown pictorially. Scale not given.